Teletrial implementation in early phase clinical trials: two national workshops - Jessica Freeman; Craig Underhill; William Evans; Donna Long; Sam Harris; Kate Burbury; Anne Woollett; Mark Buzza (Trials)
Abstract Teletrials aim to improve equity of access to clinical trials and increase clinical trial activity, especially for people with cancer in regional and rural communities. Three cancer programs, using a collective impact framework, form the Victorian Teletrial Collaborative (VTC) to enhance the uptake of teletrials. The VTC conducted two workshops with a focus on early-phase clinical trials with national stakeholders; the collaborative was able to clarify various perspectives regarding the barriers and enablers to the implementation of the teletrial model for use in early-phase clinical trials. The first workshop identified a range of barriers and enablers, while the second workshop explored the specificity of these insights to early phase teletrials. It was concluded that the identified barriers were generic to all trials utilising the teletrial model, multicentre trials early phase trials more generally. An action plan addressing six key themes has been developed to support the coordination of a national effort to progress trial activity in early phase teletrials.